A Scoping Literature Review about Impact of Lesson Study on Teacher Pedagogy: Effective Solutions in Learning Practices - Aryanti; Hikamudin, Eviana; Muryanto, Rusdiono; Peniasiania, Dian; Heryani, Rina (Universitas Pendidikan Ganesha, 2024)
Lesson Study has been recognized as an effective solution in teachers' pedagogical development, focusing on collaboration, reflection, and continuous improvement in teaching practices. Meanwhile, teacher pedagogy is a crucial element in the learning process that directly impacts student achievement or learning outcomes. Through a scoping literature review using the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) approach, this research aims to explores the impact of Lesson Study on teacher pedagogy, identifying its impacts, challenges faced, and opportunities that exist in the last decade for future research and educational practice. Article data were obtained from the Scopus (n=117) and ERIC (n=7) databases, then through a screening and eligibility process, 16 articles were selected for further analysis. This Scoping Literature Review focuses on the trends in Lesson Study research, factors influencing teacher pedagogy through Lesson Study, and its effects on student achievement. The literature results show that the United Kingdom is dominant in applying Lesson Study, high school-level implementation is prevalent, and mathematics is the main subject area. Furthermore, two main categories of factors influencing teacher pedagogy through Lesson Study were identified: Collaborative Strategies and Strategic Planning. Further findings reveal that Lesson Study not only enhances students' conceptual understanding and learning outcomes but also boosts their confidence and mathematical thinking abilities. The conclusion of this research affirms the critical role of Lesson Study in the professional development of teachers, promoting significant collaboration and strategic planning to improve the overall quality of education.